PENGARUH KOMPETENSI, KOMITMEN DAN MOTIVASI TERHADAP KUALITAS PENYUSUNANANGGARAN BERBASIS KINERJA( Pada Satuan Kerja Perangkat Daerah (SKPD) Pemerintah Daerah Kabupaten/Kota di Provinsi Jambi ) - Putriana, Marissa (EDUTECH CONSULTANT, 2017)
This study aims to determine the Influence of Competence, commitment and motivation on the Quality of Performance Based Budgeting In SKPD District Government / City of Jambi simultaneously or partially. This type of research is explanatory research. The study was conducted in 86 SKPD in Government District / City in the province of Jambi. The data collection is done by distributing questionnaires, interviews and documentation. The research instrument was tested in advance with Spearman test validity and reliability testing Cronbach Alpha. Data analysis method used is the analysis Path / Path Analysis. The results showed that the competence, commitment and motivation simultaneously significant effect on the quality of performance-based budgeting, and partially competence, commitment and motivation significant positive effect on quality of Bebrasis Budgetary Performance on SKPD District Government / City in the province of Jambi.